Wnt signaling positively regulates endothelial cell fate specification in the Fli1a-positive progenitor population via Lef1 - Hubner, Kathleen; Grassme, Kathrin S.; Rao, Jyoti; Wenke, Nina K.; Zimmer, Cordula L.; Korte, Laura; Mueller, Katja; Sumanas, Saulius; Greber, Boris; Herzog, Wiebke (Developmental Biology, 2017)
During vertebrate embryogenesis, vascular endothelial cells (ECs) and primitive erythrocytes become specified within close proximity in the posterior lateral plate mesoderm (LPM) from a common progenitor. However, the signaling cascades regulating the specification into either lineage remain largely elusive. Here, we analyze the contribution of β-catenin dependent Wnt signaling to EC and erythrocyte specification during zebrafish embryogenesis. We generated novel β-catenin dependent Wnt signaling reporters which, by using destabilized fluorophores (Venus-Pest, dGFP), specifically allow us to detect Wnt signaling responses in narrow time windows as well as in spatially restricted domains, defined by Cre recombinase expression (Tg(axin2BAC:Venus-Pest)mu288; Tg(14TCF:loxP-STOP-loxP-dGFP)mu202). We therefore can detect β-catenin dependent Wnt signaling activity in a subset of the Fli1a-positive progenitor population. Additionally, we show that mesodermal Wnt3a-mediated signaling via the transcription factor Lef1 positively regulates EC specification (defined by kdrl expression) at the expense of primitive erythrocyte specification (defined by gata1 expression) in zebrafish embryos. Using mesoderm derived from human embryonic stem cells, we identified the same principle of Wnt signaling dependent EC specification in conjunction with auto-upregulation of LEF1. Our data indicate a novel role of β-catenin dependent Wnt signaling in regulating EC specification during vasculogenesis.
CRIS-Team Scopus Importer:2020-09-23
Keywords: Mesoderm; Primitive hematopoiesis; Vasculogenesis; Wnt reporter; Zebrafish